The Effects of Synchrony on Group Moral Hypocrisy - Chvaja, Radim; Kundt, Radek; Lang, Martin (Frontiers in Psychology, 2020)
Humans have evolved various social behaviors such as interpersonal motor synchrony (i.e. matching movements in time), play and sport or religious ritual that bolster group cohesion and facilitate cooperation. While important for small communities, the face-to-face nature of such technologies makes them infeasible in large-scale societies where risky cooperation between anonymous individuals must be enforced through moral judgment and, ultimately, altruistic punishment. However, the unbiased applicability of group norms is often jeopardized by moral hypocrisy, i.e., the application of moral norms in favor of closer subgroup members such as key socioeconomic partners and kin. We investigated whether social behaviors that facilitate close ties between people also promote moral hypocrisy that may hamper large-scale group functioning. We recruited 129 student subjects that either interacted with a confederate in the high synchrony or low synchrony conditions or performed movements alone. Subsequently, participants judged a moral transgression committed by the confederate toward another anonymous student. The results showed that highly synchronized participants judged the confederate’s transgression less harshly than the participants in the other two conditions and that this effect was mediated by the perception of group unity with the confederate. We argue that for synchrony to amplify group identity in large-scale societies, it needs to be properly integrated with morally compelling group symbols that accentuate the group’s overarching identity (such as in religious worship or military parade). Without such contextualization, synchrony may create bonded subgroups that amplify local preferences rather than impartial and wide application of moral norms.